Travel and adherence to antiretroviral therapy among postpartum women living with HIV in South Africa: a cross-sectional study - Mvududu, Rufaro (Department of Public Health and Family Medicine, 2020)
In sub-Saharan Africa, women are disproportionately affected by HIV. Sustained adherence to lifelong antiretroviral therapy (ART) is needed to ensure their own health and prevent transmission of HIV to their partners and their children. However, non-adherence to ART remains a substantial challenge with many associated risk factors. Travel is often reported in the qualitative literature as a barrier to ART adherence among women living with HIV, but few quantitative studies have explored this association. This research aimed to describe travel in the past year among mothers living with HIV in the Long-term Adherence and Care Engagement (LACE) study, to explore factors associated with travel, and to investigate the associations between travel and i) self-reported adherence, and ii) HIV viral load. Part A of this dissertation is the study protocol that introduces the need for this research and presents how the research will be carried out. Part B is a narrative literature review. The review summarises and synthesises existing research relating to HIV treatment and travel in sub-Saharan Africa, giving context to the dissertation. Part C is the journal “ready” manuscript. This section presents an analysis of data from the LACE study, a cross-sectional survey of women living with HIV approximately four years after they had started ART during pregnancy in Gugulethu, Cape Town. At the LACE study visit, data on short-term travel patterns (stayed away from home for 3 or more nights) in the past year and self-reported adherence in the past 30 days (using a validated three-item scale) were collected through structured questionnaires, and a blood specimen was tested for HIV viral load. Poisson regression models with robust standard errors were used to explore factors associated with travel (any versus none), self-reported adherence (100% versus <100%), and viral suppression (≤50 copies/mL). Results were reported as crude risk ratios (RR) and adjusted risk ratios (aRR) with 95% confidence intervals (CI). The results showed that among 353 women enrolled in the LACE study (mean age 32.6 years, 48% employed, 38% married/cohabiting, median 44 months postpartum) 23% (n=81) reported travelling in the past year. Of the women who travelled, most went to the Eastern Cape (90%) and travelled 1-2 times during the year (93%). Women who travelled were more likely to be married/cohabiting than women who had not travelled (aRR = 1.45; 95% Cl: 0.97 - 2.16). Only 9% of women who travelled (7 of 81) reported difficulty with ART adherence due to travel. Overall, 59% of women reported 100% adherence in the past 30 days: 52% of women who had travelled in the past year versus 61% of those who had not travelled (aRR = 0.83; 95% Cl: 0.66-1.04). Only 56% of the cohort were virally suppressed: 60% and 55% of those who had and had not travelled in the past year, respectively (aRR = 1.10; 95% Cl: 0.89-1.36). Travel in the past year was not significantly associated with self-reported adherence or viral suppression in crude or adjusted analyses. These results highlight that poor adherence and viremia were very common in this cohort of women, four years after starting ART in pregnancy. Almost a quarter of women reported travel in the past year but only a v few reported difficulties with adherence related to travel and we found no association between travel in the past year, self-reported adherence in the past 30 days or viremia. Further research is needed to understand adherence patterns during periods of travel and interventions are clearly needed to support women's long-term adherence to ART.